TRANSFORMING NARRATIVES: ENHANCING EFL LEARNERS’ WRITING WITH AI FEEDBACK - Pariyanto, Pariyanto; Tungka, Novalita Fransisca (MEDIA DIDAKTIKA, 2024)
This study investigates the impact of ChatGPT-provided formative feedback on the narrative essay writing skills of English as a Foreign Language (EFL) learners. Sixteen undergraduate students were tasked with writing narrative essays, which were evaluated pre- and post-feedback using a standardized rubric. The essays were rated by two human raters, and inter-rater reliability was confirmed (Cronbach’s alpha = .912). The results indicated significant improvements in key writing criteria, particularly in style, voice, and overall coherence, as evidenced by the paired sample t-tests. The learners also predominantly expressed positive perceptions of ChatGPT’s feedback, highlighting its clarity and usefulness in enhancing their writing. These findings demonstrate the potential of AI-driven feedback to support language learning and address resource limitations in EFL classrooms.